Stability of an infinite swept wing boundary layer with surface waviness - Thomas,C; Mughal,MS; Gipon,M; Ashworth,R (AIAA Journal, 2016)
A scheme for generating boundary layers is described and applied to an infinite sweptwing model with wavy surface deformations. Steady laminar mean flow is extracteddirectly from solutions of the Navier-Stokes system of equations, which is validatedagainst computations of a compressible boundary layer method. Furthermore, theroutines capture separated boundary layer profiles, overcoming the constraints of theconventional methods. The stability of crossflow disturbances is investigated using bothPSE and LNS methods and the effect of chordwise waviness of variable wavelength,amplitude and phase is considered. Wavy surfaces are found to influence the growthof crossflow disturbances, suggesting that the onset of transition may also be affectedby the variations in the surface geometry.